Impact of home‐ and community‐based services in the long‐term care insurance system on outcomes of patients with acute heart failure: Insights from the Kitakawachi Clinical Background and Outcome of Heart Failure Registry. Issue 10 (19th August 2020) - Takabayashi, Kensuke; Fujita, Ryoko; Iwatsu, Kotaro; Ikeda, Tsutomu; Morikami, Yuko; Ichinohe, Tahei; Yamamoto, Takashi; Takenaka, Kotoe; Okuda, Miyuki; Nakajima, Osamu; Koito, Hitoshi; Terasaki, Yuka; et al.
Abstract : Aim: In Japan, the long‐term care insurance (LTCI) system is important for elderly people living at home; however, no clinical studies have revealed a relationship between home‐ or community‐based services and outcomes in patients with acute heart failure (AHF). Methods: This was a prospective multicenter cohort study of patients with AHF enrolled between April 2015 and August 2017. Patients aged ≥65 years with LTCI were divided into those receiving home‐ and community‐based services (service users) and without home and community‐based services (service non‐users). The endpoint was defined as a composite endpoint, which included all‐cause mortality and hospitalization for heart failure after discharge. Subgroup analyses were performed for elderly patients (<85 years) or super‐elderly patients (≥85 years). Results: The study participants were eligible for LTCI two times more than community‐dwelling people were. At the 1‐year follow‐up period, the rate of the composite endpoint showed no significant difference between service users and service non‐users among all patients or super‐elderly patients. However, in elderly patients, the rate of the composite endpoint was significantly lower among service users than service non‐users. The difference was independently maintained even after adjustments for differences in comorbidities or in social backgrounds (adjusted hazard ratio 0.62; 95% confidence interval 0.38–0.99, and adjusted hazard ratio 0.57; 95% confidence interval 0.35–0.90, respectively). Conclusions: In this study, adverse events following discharge of patients with AHF who used home‐ and community‐based services were prevented only in elderly patients, not in super‐elderly patients. Geriatr Gerontol Int 2020; 20: 967–973 .